Influencia de la composición corporal en la potencia de salto en atletas de voleibol femenino - Frade Nápoles, D.; Yáñez, R. R.; Carvajal Veitia, W.; Deturnell, Y.; Castillo, M. E. (Revista Cubana de medicina del deporte y la cultura fisica, 2020)
Introduction: In the physical performance of volleyball athletes, body composition and the maximum mechanical power developed by the muscles are essential factors in their performance. Objective: To analyze the influence of body composition on jumping power in a sample of players from the Cuban women's national indoor volleyball team. Materials and Methods: The sample consisted of 8 women from the Cuban national team for seniors in indoor volleyball. The Bosco test was applied in four modalities to determine the jump power values. MBCA Electrical Bioimpedance was used for the analysis of body composition. Through the protocol of the International Society for the Advancement of Kineanthropometry, the anthropometric evaluation of the sum of six folds was carried out. Spearman's correlation test was applied. Results: The squat jump showed inverse correlations with respect to body weight and skeletal muscle mass of the trunk. The greater the sum of skin folds in the countermovement jump, the lower the power developed. At high values of height, fat mass, fat mass index and sum of folds, discrete Abalacov values were reported. The jump jump showed high correlations with muscle mass, skeletal muscle mass, and skeletal muscle mass of the left arm. Conclusions: It was determined that in the power of the jump, fat has a negative influence and muscle mass has a positive influence